AI-ENHANCED DISASTER RECOVERY: A COLLABORATIVE APPROACH - Suhas Lakum, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The revolutionary incorporation of artificial intelligence in disaster recovery frameworks is examined in this extensive article, which highlights the critical balance between human oversight and technological innovation. The article looks at how traditional disaster recovery strategies have been transformed by AI-driven solutions in a number of industries, most notably healthcare and financial services. It shows how AI significantly improves organizational resilience through a thorough examination of case studies, implementation tactics, and best practices. The article highlights the critical role of human experience in strategic planning and decision-making while encompassing essential elements of contemporary DR solutions, such as automated failover systems, anomaly detection, and predictive analytics. It also sheds light on effective implementation strategies, highlighting the significance of thorough testing, staggered deployment, and ongoing performance metrics monitoring.